Daily bathing with 4% chlorhexidine gluconate in intensive care settings: a randomized controlled trial. (June 2019) - Pallotto, C.; Fiorio, M.; De Angelis, V.; Ripoli, A.; Franciosini, E.; Quondam Girolamo, L.; Volpi, F.; Iorio, P.; Francisci, D.; Tascini, C.; Baldelli, F.
Abstract: Objectives: To investigate whether daily bathing with a soap-like solution of 4% chlorhexidine (CHG) followed by water rinsing (CHGwr) would decrease the incidence of hospital-acquired infections (HAI) in intensive care settings. Methods: Randomized, controlled trial; infectious diseases specialists were blinded to the intervention status. All patients admitted to the Intensive Care Unit (ICU) and to the Post-operative Cardiosurgical Intensive Care Unit (PC-ICU) of the University Hospital of Perugia were enrolled and randomized to the intervention arm (daily bathing with 4% CHGwr) or to the control arm (daily bathing with standard soap). The incidence rate of acquisition of HAI was compared between the two arms as primary outcome. We also evaluated the incidence of bloodstream infections (BSI), central-line-associated BSI (CLABSI), ventilator-associated pneumonia (VAP) and catheter-associated urinary tract infections (CAUTI), and 4% CHGwr safety. Results: In all, 449 individuals were enrolled, 226 in treatment arm and 223 in control arm. Thirty-four individuals of the 226 (15%) and 57 (25.6%) suffered from at least an HAI in the intervention and control arms, respectively (p 0.008); 23.2 and 40.9 infections/1000 patient-days were detected in the intervention arm and control arm, respectively (p 0.037). The incidence of all bloodstream infections (BSI plus CABSI) was significantly reduced in the intervention arm (9.2 versus 22.6 infections/1000 patient-days, p 0.027); no differences were observed in the mortality between the two arms. Conclusions: Daily bathing with 4% CHGwr significantly reduced HAI incidence in intensive care settings. ClinicalTrial.gov registration: NCT03639363.